Menopause and the risk of metabolic syndrome among middle-aged Chinese women. Issue 1 (1st March 2015) - Strand, Mark A.; Huseth-Zosel, Andrea; He, Meizi; Perry, Judith
Abstract : Objective: This study explored the relationship between menopause and metabolic syndrome (MetS), stroke, hyperlipidemia, diabetes and hypertension. Study design: This cross-sectional study surveyed 440 women in Yuci, China in 2012. Main outcome measures: MetS, diabetes, hypertension, hyperlipidemia, stroke, and behavioral and demographic variables. Results: The prevalence of MetS in this study was 40.28% to 49.66% ( p =0.065) among pre- and post-menopausal women, respectively, after adjusting for age. Conclusions: The prevalence of diabetes, stroke, hypertension, and hyperlipidemia was higher among post- than pre-menopausal women. Health screenings for women in China should consider the increased risk for metabolic disorders during the postmenopausal stage of life.